AIHce 2004 2004
DOI: 10.3320/1.2758410
|View full text |Cite
|
Sign up to set email alerts
|

374. Urinary Bromide and Breathing Zone Concentrations of 1-Bromopropane From Workers Exposed to Flexible Foam Spray Adhesives

Abstract: Bromopropane (1-BP) has been marketed as an alternative for ozone depleting solvents and suspect carcinogens and is in aerosol products, adhesives and solvents used for metal, precision and electronics cleaning. Toxicity of 1-BP is poorly understood, but it may be a neurologic, reproductive and hematologic toxin. Sparse exposure information prompted this exposure assessment study using air sampling, and measurement of urinary metabolites. Mercapturic acid conjugates are excreted in urine from 1-BP metabolism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Geometric mean concentrations and 95% confidence intervals calculated from the urine specimens collected over the sequential time periods at these vapor degreasing plants and at foam cushion factories (Hanley et al 2006) are plotted in Figs. 2 and 3, respectively, for urinary Br cr (-) and AcPrCys cr concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric mean concentrations and 95% confidence intervals calculated from the urine specimens collected over the sequential time periods at these vapor degreasing plants and at foam cushion factories (Hanley et al 2006) are plotted in Figs. 2 and 3, respectively, for urinary Br cr (-) and AcPrCys cr concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Urinary Br (-) elevated substantially above normal (reference value = 10 mg/l) represents accumulated exposure over the previous week or two, as Br (-) is excreted slowly (Jones and Walsh 1979). Hanley et al (2006) demonstrated that urinary Br (-) is an effective biomarker of 1-BP for highly exposed foam cushion workers exposed to spray adhesives [Geometric mean (GM) = 92 ppm for sprayers; GM = 11 ppm for other jobs].…”
Section: Introductionmentioning
confidence: 98%
“…The authors stated that this disparity may be due to the absorption of 1-BP by the skin when the sprayers handled the wet adhesive with bare hands. The results of Hanley et al [2006] indicate that 1-BP may be absorbed via the skin, thus contributing to the systemic dose. Skin Notation Profiles | 1-Bromopropane 4…”
Section: -Bromopropanementioning
confidence: 96%
“…Other case reports also detailed nervous system effects [Ichihara et al , 2004a[Ichihara et al , 2004bMajersik et al 2007;Raymond and Ford 2007]. Hanley et al [2006] assessed occupational exposures to 1-BP through air sampling and urinary testing for bromide (Br-) concentrations (a known biomarker of 1-BP exposure) in workers employed as either adhesive sprayers or nonsprayers at foam-fabricating plants that used a spray adhesive containing 1-BP during the manufacture of polyurethane seat cushions. One of the reported findings included a lower than expected correlation between urinary Br-concentration and time-weighted average (TWA) for sprayers, where the mean urinary Br-concentrations for sprayers were approximately 4 times greater than non-sprayers.…”
Section: -Bromopropanementioning
confidence: 99%
“…The National Toxicology Program has concluded that exposure to 1-BP is toxic to the developmental and reproductive health of animals 3) . Animal toxicity studies with 1-BP and human case reports of occupational exposures to 1-BP have raised concerns that exposure to 1-BP might cause reproductive and neurologic effects [4][5][6][7][8] . A recent Morbidity and Mortality Weekly Report article highlighted two cases of workers diagnosed with clinical manifestations of neurotoxicity after use of 1-bromopropane in degreasing and dry cleaning operations 9) .…”
mentioning
confidence: 99%